ANALISIS PROBLEMATIKA GURU PENDIDIKAN JASMANI BERKAITAN SARANA DAN PRASARANA: STUDI KUALITATIF DESKRIPTIF PADA GURU DI GUGUS II KECAMATAN TANETE RIATTANG BARAT KABUPATEN BONE - Muliadi, Muliadi; Sudarto, Sudarto; Rahma, Rahma (Journal of Innovation Research and Knowledge, 2022)
This research is a descriptive qualitative research that aims to find out the problems of physical education teachers related to facilities and infrastructure: a descriptive qualitative study on teachers in SD cluster II, Tanete Riattang Barat sub-district, Bone district. Research data obtained through observation sheets and interviews Data analysis techniques are data reduction, data presentation, and conclusions. The results of this study indicate that in the category of physical education facilities in the sport of soccer, there are 4 schools that have met the standards, while 3 of them have not met the standards. As for the volleyball branch, there are 4 schools that have met the standards, while 3 of them have not met the standards. In athletics there are 4 schools that have met the standards while 3 of them have not met the standards. And in the gymnastics branch there are 5 schools that have met the standards and 2 of them have not met the standards. From the results of this study, the ability of schools to procure facilities and infrastructure for standard physical education subjects is limited, schools find it difficult to add sports facilities and infrastructure needed in the implementation of physical education subjects due to lack of land and sources of school funding in the form of school operational funds from local governments.